Advances in group processes. - Thye, Shane R.; Lawler, Edward J. (Advances in group processes, 2018)
"Advances in Group Processes" publishes theoreticalanalyses, reviews, and theory-based empirical chapters on group phenomena. The series adopts a broad conception of "group processes." This includes work ongroups ranging from the very small to the very large, and on classic and contemporarytopics such as status, power, trust, justice, social influence, identity,decision-making, intergroup relations, and social networks.Volume 35 brings together papers related to a variety of topics in small groups andorganizational research. The volumeincludes papers that address theoretical and empirical issues relating toconsumer behavior, vocal accommodation, measuring aggression, social identitytheory, and criminal sentencing. Othercontributions examine reverse discrimination, perceptions of responsibility for the behaviors of others, and expectations and coordination in small groups. Overall, the volume includespapers that reflect a wide range of theoretical approaches from leadingscholars who work in group processes.